Pragmatic development of Chinese during study abroad: A cross-sectional study of learner requests - Ren, Wei (Journal of pragmatics, 2019)
Pragmatic studies of learners' development during study abroad (SA) have mainly focused on English as the target language, whereas limited research has investigated Chinese, particularly over extended periods of stay. This study cross-sectionally explores the effect of SA on learners' L2 Chinese requests, with a focus on long SA durations. Data were collected through six role plays from 40 learners in China, who were classified into three groups according to their length of stay (LoS). Fifteen Chinese students were also recruited to provide native speaker data for comparison. The results indicated that, compared with native speakers, learners produced fewer direct but more indirect request strategies and fewer external and internal modifiers. Learners increasingly favoured conventionally indirect request strategies as they studied longer in China, indicating non-target-like development. External modification devices were comparatively easier for learners to acquire, as revealed by similarities in the situational distributions between learners and native speakers and among learner groups. Internal modification posed more difficulties for learners, although their abilities to employ internal modifiers developed with increasing LoS. The effect of SA on learners' pragmatic development is discussed in relation to different natures of pragmatic aspects, LoS, prior L2 proficiency, contact with native speakers, and living arrangements during SA. •This study investigates the effect of study abroad on learners' L2 Chinese requests.•The study was designed with a focus on longer study abroad (SA) durations.•Learners favoured conventionally indirect requests more as the length of stay extended.•Compared with external modifiers, internal modifiers posed greater difficulties.•The effect of SA duration on learners' pragmatic development is a complex issue.